THE IMPLEMENTATION OF SCIENTIFIC APPROACH ON BIOLOGY LEARNING GRADE X STATE HIGH SCHOOL VIEWED BY TEACHER’S EMPLOYMENT STATUS - Hefi Marrdias Siwi; Dwi Maihidin Pahlifi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This research aimed to examine the implementation of a scientific approach on biology learning of grade X state senior high school in Wonogiri viewed from teacher's employment status. It is descriptive research using the observation method. The subject involved Biology teachers of grade X and the students of grade X as many as 1 class from each school. Employing a convenience sampling technique, the researchers selected a sample of 6 biology teachers from grade X. The independent variable was the biology teacher's employment status, and the dependent variable was the scientific implementation approach on biology learning. The instrument used in this research was an observation sheet. The acquired data then analyzed descriptively. The research results have indicated that biology teachers' employment status who is a civil servant or non-civil servant has implemented the scientific approach well. The students' involvement and activity were positive during the learning process.